Profile of Risk Factors for Noncommunicable Diseases Among the Migrants of Santal Tribe Residing in Bhubaneswar City, Odisha, India - Pradhan, Himanshu Sekhar; Mappillairaju, Bagavandas (National Journal of Community Medicine, 2025)
Background: Risk factors of Noncommunicable diseases (NCDs) are increasing among Indian tribes. However, this issue remains unexplored in migrants of Odisha’s Santal tribe, in Bhubaneswar city. Objective: To assess the prevalence of behavioural and selected metabolic risk factors of NCDs among Santal migrants aged 18 to 69 years in Bhubaneswar. Methodology: A cross-sectional study involving 516 Santal migrants was conducted from September to December 2022 using the WHO STEPS survey questionnaire. Descriptive statistics and logistic regression analyses were performed using R statistical software. Results: Prevalence of tobacco and alcohol use were 80% (95% CI: 76.3–83.3) and 81.8% (95% CI: 78.1–85.0), respectively with higher rates among males. Low physical activity was reported by 30.6% (95% CI: 26.7–34.8), commonly among females. 98.8% participants had inadequate fruit and vegetable intake. Hypertension was found in 40.3% (95% CI: 36.1–44.7), abdominal obesity in 33.5% and obesity in 28.5%. Conclusions: High prevalence of NCD risk factors was observed among Santal migrants with inadequate intake of fruits and vegetables, followed by alcohol and tobacco use being most prevalent. Male gender was independently linked to tobacco and alcohol use; age 45-69 years with alcohol use and low education with tobacco use. Culturally appropriate, community-based health promotion programs could be beneficial.